DSC assessment on curing degree of micron-scaled adhesive layer in lamination-pressed flexible printed circuit panels / Kok-Tee Lau, Hoi Ern Kok and Nur Hazirah Rosli - Lau, Kok-Tee; Hoi, Ern Kok; Rosli, Nur Hazirah (Universiti Teknologi MARA, 2021)
Continuous monitoring and optimisation of the lamination process are critical in negating flexible printed circuit (FPC) delamination risk during operation. The main QC inspection criterion of the lamination adhesive's curing degree is adhesive thickness. However, this method is prone to measurement error due to poor microscopy image definition and the inspector's measurement parallax error. The feasibility of using thermal characterisation to measure the difference in curing degrees of micron-scaled adhesive layer of laminated FPC was investigated. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were used according to IPC standards. Polyimide-epoxy adhesive coverlays were laminated onto both sides of FPC at 120 kgf/cm2 pressure and 180 °C temperature for 120 s. Then, the coverlays were subjected to oven curing at 150 °C for 60 min. The DSC detected a small difference in the curing degree of adhesive layers in the two cured FPC laminated in different laminating-press openings (T1 and T2). T2 had a glass transition temperature (Tg) of 106.5 °C, which was higher than that for T1 (105 °C), thereby suggesting that the former had a higher curing degree than the latter. This result was consistent with the adhesive thickness measurement result of the DSC samples. The adhesive thickness of T2 was smaller (30.97 µm) than that of the T1 (31.76 µm). T2 had a higher curing degree than T1 because of the larger shrinkage percentage. In comparison with DSC, TGA was unable to detect the curing degree difference between the samples because of the undetected weight loss resulting from the adhesive curing.